1982
DOI: 10.1128/iai.35.1.151-156.1982
|View full text |Cite
|
Sign up to set email alerts
|

Permissiveness of rabbit monocytes and macrophages for herpes simplex virus type 1

Abstract: The permissiveness of rabbit monocytes and macrophages for herpes simplex virus was examined. Peripheral blood monocytes, alveolar macrophages, and peritoneal exudate macrophages were studied for their ability to replicate herpes simplex virus strains RE and KOS. Results indicated different degrees of interaction with virus depending on the macrophage type. Only peritoneal exudate macrophages showed evidence of virus replication. Productive infection was limited, with only a small number of cells (0.02%) yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A number of variables in the experimental procedure may influence the outcome of the intrinsic virus-macrophage interaction [4]. Among these, mention may be made of the source of macrophages [8,9], the use of non-specific irritants to increase macrophage yields [10] and culture conditions like the serum type and concentration [11], the presence of antiviral antibody [12] and precultivation of the cells [2,10]. Macrophages are generally more restrictive for virus replication than most other cell types [4].…”
Section: Intrinsic Virus-macrophage Interactionmentioning
confidence: 99%
“…A number of variables in the experimental procedure may influence the outcome of the intrinsic virus-macrophage interaction [4]. Among these, mention may be made of the source of macrophages [8,9], the use of non-specific irritants to increase macrophage yields [10] and culture conditions like the serum type and concentration [11], the presence of antiviral antibody [12] and precultivation of the cells [2,10]. Macrophages are generally more restrictive for virus replication than most other cell types [4].…”
Section: Intrinsic Virus-macrophage Interactionmentioning
confidence: 99%
“…Our laboratory has been investigating several aspects of the interaction between HSV and M0 of adult New Zealand white rabbits. In a recent study of M0 permissiveness to HSV infection, we found different levels of interaction with HSV, which appeared to relate to the state of M0 differentiation (21). The present report compares the effects of in vitro exposure to HSV on alveolar M0 (AM) and peritoneal exudate MO (PEM) function.…”
mentioning
confidence: 72%
“…AM were obtained from adult New Zealand white rabbits by lavage of excised lungs (18). PEM were obtained after elicitation by intraperitoneal inoculation of sterile paraffin oil (21). The RE strain of HSV type 1 (6) was prepared in Vero cells as previously described (21,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TCIDo, 50%o tissue culture infective dose. (10,23). Thus, in the CAEV syndrome, our data suggest that monocytes migrating from the circulation into the infected joint would be susceptible to virus infection and thereby may aid in perpetuating instead of eliminating the infection.…”
mentioning
confidence: 79%